Phenotypic and genotypic antimicrobial resistance correlation and plasmid characterization in Salmonella spp. isolates from Italy reveal high heterogeneity among serovars - Sara Petrin; Sara Petrin; Massimiliano Orsini; Andrea Massaro; John E. Olsen; Lisa Barco; Carmen Losasso (Frontiers in Public Health, 2023)
IntroductionThe spread of antimicrobial resistance among zoonotic pathogens such as Salmonella is a serious health threat, and mobile genetic elements (MGEs) carrying antimicrobial resistance genes favor this phenomenon. In this work, phenotypic antimicrobial resistance to commonly used antimicrobials was studied, and the antimicrobial resistance genes (ARGs) and plasmid replicons associated with the resistances were determined.MethodsEighty-eight Italian Salmonella enterica strains (n = 88), from human, animal and food sources, isolated between 2009 and 2019, were selected to represent serovars with different frequency of isolation in human cases of salmonellosis. The presence of plasmid replicons was also investigated.Results and discussionResistances to sulphonamides (23.9%), ciprofloxacin (27.3%), ampicillin (29.5%), and tetracycline (32.9%) were the most found phenotypes. ARGs identified in the genomes correlated with the phenotypical results, with blaTEM-1B, sul1, sul2, tetA and tetB genes being frequently identified. Point mutations in gyrA and parC genes were also detected, in addition to many different aminoglycoside-modifying genes, which, however, did not cause phenotypic resistance to aminoglycosides. Many genomes presented plasmid replicons, however, only a limited number of ARGs were predicted to be located on the contigs carrying these replicons. As an expectation of this, multiple ARGs were identified on contigs with IncQ1 plasmid replicon in strains belonging to the monophasic variant of Salmonella Typhimurium. In general, high variability in ARGs and plasmid replicons content was observed among isolates, highlighting a high level of heterogeneity in Salmonella enterica. Irrespective of the serovar., many of the ARGs, especially those associated with critically and highly important antimicrobials for human medicine were located together with plasmid replicons, thus favoring their successful dissemination.